Optimalisasi Peran Orang Tua Dalam Menanamkan Nilai-Nilai Islam Pada Anak Dalam Keluarga - Khairunnisa Khairunnisa (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
This article discusses methods able to be applied in familiarizing Islamic values to children. Efforts to optimalize parents’ roles in familiarizing Islamic values, preschool children, and Islamic education will be emerged. This article also presents some Islamic education methods in family with their own advantages and disadvantages. Therefore, as parents, in this case as educators in family, we have options to select the finest methods to be used. It can be done by combining some methods in order to minimalize the disadvantages of certain method use.